2014
DOI: 10.7869/tg.185
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of normal portal vein diameter in children

Abstract: Background and aim: The internal diameter of the portal vein varies with age and anthropometric parameters. The caliber of the normal portal vein in adults has been extensively studied but little is known about portal vein dimensions in the growing child. This study was conducted to establish standards of portal vein diameter by ultrasonography in healthy Indian children based on age, gender and anthropometric parameters. Methods: Total 306 healthy children between the age of <1 month and 12 years, visiting ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
2
5
0
Order By: Relevance
“…In this study, the mean portal vein diameter was found to be slightly higher in males than females, but the difference was not statistically significant at p<0.05 level. This finding is consistent with the results of other studies, such as Hawaz et al 2 and Ghosh et al 3 , who also found no significant influence of gender on portal vein diameter.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the mean portal vein diameter was found to be slightly higher in males than females, but the difference was not statistically significant at p<0.05 level. This finding is consistent with the results of other studies, such as Hawaz et al 2 and Ghosh et al 3 , who also found no significant influence of gender on portal vein diameter.…”
Section: Discussionsupporting
confidence: 93%
“…2 A major abnormality of the portal venous system is portal hypertension, which is caused by an increase in resistance to portal blood flow that is caused by alterations in liver architecture that cause an enlargement of extrahepatic and intrahepatic portal vessels and the formation of portosystemic collaterals. 3 The formation of portosystemic collaterals may lead to splenomegaly, ascites, encephalopathy among others. 4 To evaluate patients suspected of having portal thrombosis, diagnostic imaging methods such as portal venography, splenoportography, and arteriography have been used.…”
Section: Introductionmentioning
confidence: 99%
“…We have also scrutinized the relation between waist circumference and the diameters of intraabdominal veins. There has been few studies published up to date and investigated pediatric portal vein diameters in the healthy pediatric population in several nations by the US (3,4). Ghosh et al found positive correlation between the portal vein diameter and age, height, weight and chest circumference without any difference between boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CT-based normative data could be provided for children. There have been previous studies investigating portal vein diameters and vena cava inferior of children on US with a limited number of cases (1)(2)(3)(4)(5)(6). Due to the operator dependence of US, the diameters would be variable based on position, respiratory phase and probe direction.…”
Section: Introductionmentioning
confidence: 99%
“…Portal vein diameter measurements are available for 306 children from India, including PSAC, by height. 40 However, the majority of studies reporting organometry report the results of children >80 or 100 cm, 41,42 making it difficult to generalize to the smaller PSAC population.…”
Section: Discussionmentioning
confidence: 99%